2004
DOI: 10.1007/s11661-004-1001-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging and deformation on the microstructure and properties of Fe−Ni−Ti maraging steel

Abstract: The age-hardening behavior of Fe-25.3Ni-1.7 Ti (wt pct) alloy both in undeformed specimens and in specimens cold deformed by 10 or 20 pct prior to aging was studied. The microstructural changes during aging were observed using transmission electron microscopy (TEM) and atom probe analysis and there were related to the mechanical properties as measured by microhardness and shear punch testing. An excellent combination of hardness, strength, and ductility was achieved after only 5 seconds aging at 550°C. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…It could be suggested that Ti+Al-rich clusters together with substrucure were preferential nucleation sites for this precipitation. Based on TEM data, there was a long standing debate regarding the exact shape of Ni 3 Ti precipitates in maraging steels being plate-like [16], needlelike [23][24][25] or rod-like [24,26]. As we now could conclude, both plate and rod morphologies of these precipitates co-exist at certain stages of decomposition.…”
Section: Decomposition Of Martensite In Maraging Steelmentioning
confidence: 87%
See 1 more Smart Citation
“…It could be suggested that Ti+Al-rich clusters together with substrucure were preferential nucleation sites for this precipitation. Based on TEM data, there was a long standing debate regarding the exact shape of Ni 3 Ti precipitates in maraging steels being plate-like [16], needlelike [23][24][25] or rod-like [24,26]. As we now could conclude, both plate and rod morphologies of these precipitates co-exist at certain stages of decomposition.…”
Section: Decomposition Of Martensite In Maraging Steelmentioning
confidence: 87%
“…FeNiTi (Mn,Al) maraging steels exhibit an unusual rapid hardening phenomenon after just 5 s ageing at 550 o C [14][15][16][17]. In this condition it achieves approximately 50% of the maximum increase in strength without significant sacrifices in ductility.…”
Section: Introductionmentioning
confidence: 99%
“…The g-phase exhibits a hexagonal lattice with a = 0.255 nm and c = 0.42 nm [22]. The orientation relationship between the g-phase and the martensitic matrix was found to be (0 1 1) M ||(0 0 0 1) g ; [1][2][3][4][5][6][7][8][9][10][11] M || [11][12][13][14][15][16][17][18][19][20] g [21,[23][24][25]. In the literature some debate exists on the mechanism of formation of the g-phase.…”
Section: Introductionmentioning
confidence: 99%
“…In the as-quenched condition, the microstructure contained martensite with~5 pct retained austenite in the form of thin layers between the martensite laths. [11,16] The samples were aged in a salt bath for 5 to 3600 seconds at 550°C. Needle-shaped atom probe specimens were prepared with a standard two-stage electropolishing procedure.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8] The improved properties achieved in these newer steels are associated with the formation of Ni 3 Ti and Fe 2 (Mo,Ti) precipitates, which strengthen the alloys through the operation of Orowan-type mechanisms. The morphology of the Ni 3 Ti particles was found to be needle-like, [7,[9][10][11][12] plate-like, [11] or rod-like. [4,7] In addition, unidentified spherical precipitates were detected in the matrix.…”
Section: Introductionmentioning
confidence: 99%